Evolutionary Pattern of Interferon Alpha Genes in Bovidae and Genetic Diversity of IFNAA in the Bovine Genome - Peters, Sunday O.; Hussain, Tanveer; Adenaike, Adeyemi S.; Hazzard, Jordan; Morenikeji, Olanrewaju B.; De Donato, Marcos; Paul, Sujay; Babar, Masroor; Yakubu, Abdulmojeed; Imumorin, Ikhide G. (Frontiers in Immunology, 2020)
Interferons are secretory proteins induced in response to specific extracellular stimuli which stimulate intra- and intercellular networks for regulating innate and acquired immunity, resistance to viral infections, and normal and tumor cell survival and death. Type 1 interferons plays a major role in the CD8 T-cell response to viral infection. The genomic analysis carried out here for type I interferons within Bovidae family shows that cattle, bison, water buffalo, goat and sheep (all Bovidae), have different number of genes of the different subtypes, with a large increase in the numbers, compared to human and mouse genomes. A phylogenetic analysis of the IFNA proteins in this group shows that the genes do not follow the evolutionary pattern of the species, but rather a cycle of duplications and deletions in the different species. We also studied the genetic diversity of the bovine IFNAA, as an example of the IFNA genes in cattle, sequencing a fragment of the coding sequence in 18 breeds of cattle from Pakistan, Nigeria and USA. Similarity analysis allowed the allocation of sequences into 22 haplotypes. Bhagnari, Brangus, Sokoto Gudali and White Fulani, had the highest number of haplotypes, while Angus, Hereford and Nari Master had the least. However, when analyzed by the average haplotype count, Angus, Bhagnari, Hereford, Holstein, Muturu showed the highest values, while Cholistani, Lohani and Nari Master showed the lowest values. Haplotype 4 was found in the highest number of individuals (74), and in 15 breeds. Sequences for yak, bison and water buffalo, were included within the bovine haplotypes. Medium Joining network showed that the sequences could be divided into 4 groups: one with highly similar haplotypes containing mostly Asian and African breeds, one with almost all of the Bos taurus American breeds, one mid-diverse group with mostly Asian and African sequences, and one group with highly divergent haplotypes with five N’Dama sequences and one from each of White Fulani, Dhanni, Tharparker and Bhagnari. The large genetic diversity found in IFNAA could be an indication of genetic variation among different genes of IFNA and an adaptation for these species in response to viral challenges.